PEMAKNAAN NORMA HAK ASASI MANUSIA DALAM UUD 1945 BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI - Aan Eko Widiarto; Muchamad Ali Safa'at; Mardian Wibowo (Arena Hukum, 2018)
AbstractThe authority of judicial review of Â an Act by the Constitutional Court has a strategic position in strengthening the rule of law in Indonesia, which is one of the characteristics is the recognition and protection of human rights. The Constitutional Court in exercising judicial review authority has interpreted various provisions of the 1945 Constitution on human rights. Some of which reinforce the meaning as grammatically read in the 1945 Constitution, but there are also decisions that mean differently than the grammatical meaning. This research was conducted to know the meaning of the provisions in the 1945 Constitution which regulate human rights, and to know whether through the Constitutional Court decision even change the meaning of human rights. This research method is normative juridical research. The approach used includes theoretical approach and conceptual approach. Based on the analysis of legal materials used in this study concluded that the decisions of the Constitutional Court other than affirm the meaning of human rights as contained in the 1945 Constitution, the Constitutional Court through its decision also has shifted (expand) some of the meaning of human rights contained in the 1945 Constitution.Â AbstrakKewenangan pengujian undang-undang oleh Mahkamah Konstitusi menempati posisi strategis dalam penguatan negara hukum di Indonesia, yang salah satu cirinya adalah adanya pengakuan dan perlindungan terhadap hak asasi manusia. MK dalam menjalankan kewenangan pengujian undang-undang telah menafsirkan berbagai ketentuan UUD 1945 mengenai hak asasi manusia, yang beberapa penafsiran tersebut menguatkan makna sebagaimana secara gramatikal terbaca dalam UUD 1945 namun terdapat pula putusan yang memaknai secara berbeda dibandingkan makna gramatikal UUD 1945. Penelitian ini dilakukan untuk mengetahui makna ketentuan dalam UUD 1945 yang mengatur mengenai hak asasi manusia, serta untuk mengetahui apakah melalui putusan MK terjadi pergeseran bahkan perubahan makna hak asasi manusia dimaksud. Metode penelitian ini berbentuk penelitian yuridis normatif. Pendekatan yang digunakan meliputi pendekatan teoretis (theoretical approach), dan pendekatan konseptual (conceptual approach). Berdasarkan analisis bahan hukum yang digunakan dalam penelitian ini disimpulkan bahwa putusan-putusan MK selain menegaskan makna hak asasi manusia sebagaimana terdapat dalam UUD 1945, MK melalui putusannya juga telah menggeser (memperluas) sebagian makna hak asasi manusia yang tercantum di dalam UUD 1945.